Relationships between female-headed rural micro-enterprises and micro-enterprise assistance providers : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Rural Development at Massey University, New Zealand - Utto, Grittaya (Massey University, 2013)
Although there are financial and other services extensively provided by formal micro-enterprise assistance providers, including micro-finance institutions (MFIs) and government agencies, in order to assist female-headed rural micro-enterprises (female-headed RMEs), there is much evidence to show that these entrepreneurs still seek other services, in particular from moneylenders. Such evidence reflects the need for improvement in the relationship between formal providers and these entrepreneurs. This research aims to explore and understand existing social networks between the counterparts, the tenet underlying relationship developments. The research employs the qualitative approach, principally using purposive sampling and in-depth interview techniques. The case (thirty eight enterprises and six providers) are those operating in Khon Kaen province, Northeast Thailand — its economically poorest region of Thailand. The study found that these entrepreneurs’ social networks were limited but specific. Individual entrepreneurs (IEs) would rather develop relationships with moneylenders and (to a lesser extent) with MFIs. Relationships with government agencies are apparently absent. In contrast, community-based enterprises (CBEs) had strong relationships with government agencies, because, importantly, CBEs are fully supported by these agencies. The study found the establishment of certain CBEs was initiated by government agencies, although community members may not have had their own intentions to do so. The viability of such enterprises is solely dependent on the financial grants provided by the agencies. In order to gain resources for operating enterprises, IEs are willing to become indebted with loans issued by local moneylenders, whilst nearly all members of CBEs will solely apply for further grants from the providers. The members will leave the enterprises, if they become liable for debt incurred after joining a CBE. The research findings highlight that the characteristics of entrepreneurs are key factors affecting their relationship development with the providers. Small-scale activities, such as those of retailers and vendors, chiefly specified their relationships with moneylenders who promptly responded to their financial needs. Meanwhile, micro-entrepreneurs involved in larger scale activities tended to apply for assistance from government departments. The Relationships between female-headed RMEs and micro-enterprise assistance providers findings suggest that the absence of service branches of formal providers, at (or nearby) villages where entrepreneurs reside, could push them to apply for services from moneylenders. Whilst there is limited evidence of gender discrimination, female entrepreneurs prefer not to develop relationships with formal providers because they perceive that the application procedure for the formal providers is time-consuming. The entrepreneurs, accordingly, leave the application for their husbands to deal with. The female entrepreneurs would rather seek loans from the moneylenders, who, typically, provide quick services with minimal document requirements. The present work provides insights into social networks, in addition to relationship development and the key factors affecting relationships. These insights could be beneficial in assisting practitioners and providers, when they design and implement services consistent with the needs of female-headed RMEs.
Keywords: Economic assistance; Social aspects; Businesswomen; Rural women; Microfinance; Small business; Economic conditions; Thailand; Micro-enterprises